Intergroup and intragroup dimensions of COVID-19: A social identity perspective on social fragmentation and unity. (February 2021) - Abrams, Dominic; Lalot, Fanny; Hogg, Michael A.
COVID-19 is a challenge faced by individuals (personal vulnerability and behavior), requiring coordinated policy from national government. However, another critical layer—intergroup relations—frames many decisions about how resources and support should be allocated. Based on theories of self and social identity uncertainty, subjective group dynamics, leadership, and social cohesion, we argue that this intergroup layer has important implications for people's perceptions of their own and others' situation, political management of the pandemic, how people are influenced, and how they resolve identity uncertainty. In the face of the pandemic, initial national or global unity is prone to intergroup fractures and competition through which leaders can exploit uncertainties to gain short-term credibility, power, or influence for their own groups, feeding polarization and extremism. Thus, the social and psychological challenge is how to sustain the superordinate objective of surviving and recovering from the pandemic through mutual cross-group effort.